Detection of genetic variation with radioactive ligands. I. Electrophoretic screening of plasma proteins with a selected panel of compounds. - Cavalli-Sforza, L L (1977)
To detect new genetic variation in human plasma proteins, a panel of 63 radioactive substances were screened as potential radioligands using polyacrylamide gel electrophoresis (PAGE) and autoradiography. Vitamins, hormones, drugs, amino acids, purines, pyrimidines, sugars and lipids labeled with 14C or other radionuclides were among those substances tested. A majority bound to albumin and a smaller fraction to prealbumins and lipoproteins. Several vitamins and hormones bound to specific alpha and beta globulins. (1) Electrophoretic polymorphisms of vitamin D-binding protein (group-specific component), a vitamin B12-binding protein (transcobalamin II), and thyroxine-binding alpha-globulin are described elsewhere. (2) Testosterone-binding beta-globulin (TeBG) showed an electrophoretic polymorphism in Caucasians and a possible deficiency allele. (3) Transcortin showed an electrophoretic doublet in all persons tested but no electrophoretic variation. (4) A protein binding derivative of norepinephrine or epinephrine was identified as transferrin. (5) A nonpolymorphic protein running cathodal to albumin and binding a derivative of riboflavin was tentatively identified as a fraction of albumin with mobility altered as a result of interaction with the ligand.